2013
DOI: 10.1363/3905813
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intrafamilial Power on Maternal Health Care in Mali: Perspectives of Women, Men And Mothers-in-Law

Abstract: Despite decades of policies and programs aimed at improving reproductive health worldwide, high maternal morbidity and mortality persist in many resource-poor settings, particularly in Sub-Saharan Africa. [1][2][3] The predominant approach to mitigating this problem has been to target the knowledge, attitudes and practices of women of reproductive age and to strengthen health service provision. Although educating and designing services for women is undoubtedly important, this focus assumes that women have cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 44 publications
7
58
1
1
Order By: Relevance
“…For instance, lower educational levels [9] and socioeconomic factors [2,7] are associated with poor ANC attendance in women in rural areas [2,10]. Spousal support and decisions concerning the use of maternal health services also influence women’s access to skilled care [11]. This could be attributed to the patriarchal system in place in Africa, in which men are usually the heads of households, with the power and authority to make decisions, including those concerning their wives’ use of maternal health services [1216], for their family members [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, lower educational levels [9] and socioeconomic factors [2,7] are associated with poor ANC attendance in women in rural areas [2,10]. Spousal support and decisions concerning the use of maternal health services also influence women’s access to skilled care [11]. This could be attributed to the patriarchal system in place in Africa, in which men are usually the heads of households, with the power and authority to make decisions, including those concerning their wives’ use of maternal health services [1216], for their family members [13].…”
Section: Introductionmentioning
confidence: 99%
“…Husbands' preferences and opinions were not associated with any outcome. [5] Our study found that 75% of men decided which hospital to go to and family size decision. This finding is close to the study done by Azuh D, Fayomi O and Ajayi which found that in family decision making power including that of health and treatment place, the patriarchal domination orchestrated by gender roles manifested prominently as husband exercises an overwhelming proportion (72.7%) or control in the affairs of his household activities.…”
Section: Discussionmentioning
confidence: 68%
“…Daughters-in-law were not mentioned by these women, even though they typically lived together in the same household. This limitation of communication between mothers-in-law and daughters-in-law is part of the cultural rules that define their relationship and was to be expected (White et al 2013). Women from all age groups showed interest in attending the cuisines collectives.…”
Section: Cuisines Collectives In Practicementioning
confidence: 99%